Cover Picture: Probing the S1′ Site for the Identification of Non‐Zinc‐Binding MMP‐2 Inhibitors (ChemMedChem 9/2013). Issue 9 (27th August 2013) - Pizio, Antonella Di; Laghezza, Antonio; Tortorella, Paolo; Agamennone, Mariangela
<x xml:space="preserve">Abstract</x> The front cover picture shows a virtual screening protocol used to identify non‐zinc‐binding matrix metalloproteinase (MMP)‐2 inhibitors. A virtual library was filtered to obtain a drug‐like subset of molecules that was subsequently submitted to pharmacophore screening, followed by docking in the MMP‐2 (grey protein structure) binding site. The pharmacophore model employed was inspired by a known MMP‐8 inhibitor (green sticks), which was used like a probe in the MMP‐2 S1′ site (top left protein structure). Finally, visual inspection of the docking poses of the virtual hits led to the selection of 20 compounds for experimental evaluation. The virtual screening protocol identified a novel MMP‐2 inhibitor (orange sticks); modeling (bottom left protein structure) suggests that this compound does not bind to the zinc ion (purple sphere), but rather interacts with the target by other means, such as hydrogen bonds (dashed lines). For more details, see the Full Paper by Mariangela Agamennone et al. on p. 1475 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>